К истории бронепоездной техники - Ромадин, С.В. (Питання історії науки і техніки, 2008)
У статті викладаються загальні відомості про найбільш важливі етапи становлення, розвитку й бойового застосування бронепоїзної техніки. Основна увага приділена європейському театру воєнних дій, бронепоїзній справі в Російській імперії і виявленню на цьому тлі ролі й місця України. The paper presents the general information on the most essential stages of generation, development
and military use of the armored train equipment. Primary emphasis is placed on the
European theatre of military operations, armored train engineering in the Russian Empire and
USSR and on revealing the importance and rank of Ukraine against this background.